THE VALIDITY OF EXISTING SPEAKING MATERIALS BASED ON TASK BASED LEARNING - Syafrida . Matondang; Meisuri . .; Anni Holila Pulungan (LINGUISTIK TERAPAN, 2023)
Course book is one of medium that is needed so much by both teacher and learners in facilitating teaching and learning process. However, the available course books do not always match with the learners and institution needs. Fortunately, the purpose of this study was to investigate the validity of students’ existing speaking material for elementary school students grade V based on Task Based Learning at MI Swasta Mardliatul Islamiyah. The data were collected through questionnaires, interview and documentary sheet. The validity of the device was assessed by students using a validation sheet. The validation result data were analyzed descriptively quantitative and descriptive qualitative. The results of data analysis show that the students’ speaking material have not reached a valid category with the mode of score ranging from 1 to 2.